Free radical imaging of endogenous redox molecules using dynamic nuclear polarization magnetic resonance imaging. (3rd April 2021) - Hyodo, Fuminori; Ito, Shinji; Eto, Hinako; Elhelaly, Abdelazim Elsayed; Murata, Masaharu; Akahoshi, Tomohiko; Utsumi, Hideo; Matuso, Masayuki
Abstract: Redox reactions accompanied by the oxidation–reduction of endogenous molecules play important roles in maintaining homeostasis in living organisms. In humans, numerous endogenous molecules that contribute toward maintaining physiological conditions form free radicals via electron transfer. A typical example of this is the mitochondrial electron transport chain, which is involved in energy production. If free radicals derived from endogenous molecules could be visualized and exploited as biological and functional probes, redox reactions mediated by endogenous molecules could be detected non-invasively. We succeeded in visualizing the free radicals derived from endogenous molecules using an in vivo dynamic nuclear polarization (DNP) magnetic resonance imaging (MRI) system. In this review, we describe the visualization of endogenous redox molecules, such as flavins and ubiquinones, which are mitochondrial electron carriers, as well as vitamin E and vitamin C (ascorbate). In addition, we describe the application of melanin free radicals for the in vivo visualization of metabola without using probes via in vivo DNP-MRI.